Identification and Characterizations of Potential Indigenous Endophytic Bacteria which had Ability to Promote Growth Rate of Tomato and Biocontrol Agents of Ralstonia solanacearum and Fusarium oxysporum fsp. solani (Indonesian Society for microbiology, 2017)
Among Plant Growh Promoting Rhizobacteria (PGPR) groups, endophytic bacteria considered as one of the options to control vascular wilt disease because of its ability to live and colonized internal roots of plants without causing any damages. Our previous research had screened 9 isolates which had best ability to promote growth rate and increase yields of tomato and biocontrol agents of R. solanacearum and Fusarium oxysporum f.sp solani in planta condition. In order to know its abilities, those isolates need to be characterized. This research purposedto characterize those isolates abilities to produce IAA, phosphate solubilizing, siderophore production, cyanide production, NH3 production, and ability to colonize endophytically and identified the isolates using 16S rRNA. Result shown that all isolates can produce IAA, where TLE1.1 produce highest IAA concentration (42.5 ppm). Isolates E1AB1.3, TLE 1.1 and TLE2.2 can dissolved phosphate. None of the isolates produced HCN and NH3. Only TLE 2.3 isolate can produce siderophore. All of 9 isolates were identified using 16S rRNA gene using 27F and 1492R primers. All isolates were identified as different species, i.e. Bacillus toyonensis strain BCT-7112 (EPL1.1.3), Serratia nematodiphila strain DZ0503SBS1 (TLE2.3), Bacillus anthracis strain ATCC 14578 (EPL1.1.4), Bacillus cereus ATCC 14579 (TLE1.1), Bacillus cereus strain JCM 2152 (SNE2.2), Enterobacter cloacae subsp. dissolvens strain ATCC 23373 (E1.AB1.2), Serratia marcescens strain NBRC 102204 (E1AB2.1), Klebsiella michiganensis strain W14 (TLE2.2), and Chryseobacterium rhizoplanae strain JM-534 (KLE3.3).